Analyses of the Markov modulated fluid flow with one-sided phtype jumps using coupled queued and the completed graphs - Baek, Jung Woo (2014)
In this paper, we analyze Markov modulated fluid flow rocesses with one-sided ph-type jumps using the completed graph and also through the limits of coupled queueing processes to be constructed. For the models, we derive various results on time-dependent distributions and distributions of first passage times, and present the Riccati equations that transform matrices of the first return times to 0 satisfy. The Riccati equations enable us to compute the transform matrices using Newton’s method which is known very fast and stable. Finally, we present some duality results between the model with ph-type downward jumps and the model with ph-type upward jumps. This paper contains extended results of Ahn (2009) and probabilistic interpretations given by the completed graphs.